Infants with trigonocephaly treated with fronto-orbital remodelling and endocortical positioning of resorbable plates - a retrospective cohort study including 101 patients - Zittel, Sven; Ristow, Oliver; Moratin, Julius; Rückschloß, Thomas; Hoffmann, Jürgen; El Damaty, Ahmed; Freudlsperger, Christian; Engel, Michael (The journal of craniofacial surgery, 2023)
Purpose: - Fronto-orbital remodeling is the gold standard for surgical treatment of metopic synostosis in many craniofacial centers. For fixation, resorbable materials are widely used. Because of swelling during resorption, the positioning of the plates can be relevant. Therefore, the goal of this study was to investigate whether there are limitations to endocortical positioning of resorbable plates. - Methods: - In this retrospective study, all patients with metopic craniosynostosis resulting in trigonocephaly, who were treated with a standardized fronto-orbital remodeling and endocortical positioning of resorbable plates, between February 2012 and December 2019 were included. The endpoint of this study was the postoperative complications that can be attributed to the material used. - Results: - A total of 101 patients, who were treated at our unit, could be included with a male predominance, 81 (80.2%) boys versus 20 (19.8%) girls. Surgery was performed at a median age of 9 months (±2.56). No complications were seen related to resorbable plates. All patients of our study population were categorized as Whitaker classification I and II. - Conclusion: - This study shows that the risk level in using endocortical resorbable plates positioned on the inner surface of the bone is low. From an aesthetic point of view, we could not detect any disadvantage.
Gesehen am 25.09.2023